WATER ABSORPTION CAPACITY COEFFICIENT AND MASS MOISTURE OF RAMMED EARTH MATERIAL - Barbora Mužíková; Tereza Otcovská; Pavel Padevět (Acta Polytechnica CTU Proceedings)
This article presents the development of mass moisture of rammed earth material and determines the water absorption capacity coefficient for rammed earth with illite-kaoline clay. Specimens of two prescriptions were rammed in the moulds. They were settled in the box with soft foam that was moistened. The level of moistening was kept constant. The specimens were regularly measured and weighted. Two measuerements were carried out – one of montmorillonite clay during 13 days and one of illite-kaoline clay during three hours. The development of moisture increase was captured and the water absorption capacity coefficient for illite-kaoline clay was determined and compared to coefficients of common building materials.